Stroke systems of care in South-East Asia Region (SEAR): commonalities and diversities - Ivy A. Sebastian; Dorcas B.C. Gandhi; Padmavati N. Sylaja; Raju Paudel; Yogeshwar V. Kalkonde; Yangchen Yangchen; Harsha Gunasekara; Ranjit J. Injety; Pranay J. Vijayanand; Nistara S. Chawla; San Oo; Khin Myo Hla; et al. (Elsevier, 2023)
Summary: The Southeast Asia Region (SEAR) accounts for nearly 50% of the developing world's stroke burden. With various commonalities across its countries concerning health services, user awareness, and healthcare-seeking behavior, SEAR still presents profound diversities in stroke-related services across the continuum of care. This review highlights the numerous systems and challenges in access to stroke care, acute stroke care services, and health care systems, including rehabilitation. The paper has also attempted to compile information on the availability of stroke specialized centers, Intravenous thrombolysis (IVT) ready centers, Endovascular therapy (EVT) ready centers, rehabilitation centers, and workforce against a backdrop of each country's population. Lastly, the efforts of WHO (SEARO)-CMCL (World Health Organization-South East Asia region, Christian Medical College & Hospital Ludhiana) collaboration towards improving stroke services and capacity among the SEAR have been described.